Objetos entre contextos e significados: as coleções etnográficas do Museu Paraense Emílio Goeldi entre 1894 e 1905 - COELHO, Matheus Camilo (Universidade Federal do Pará, 2025)
This study aims to investigate the process of musealization of ethnographic collection placed in the Museum Paraense Emílio Goeldi (MPEG), named Lauro Sodré (1897), Henri Coudreau (1898), Frei Gil Vilanova (1902) and Koch-Grünberg (1905). Not only centered in the collector’s protagonism but comprehending the collection processes as a polysemic practice, this research intent to comprehend its role in social and political context, interests of the museums, their scientific agenda, trajectory and conceptions of the producing communities and collectors, the collaboration and circulation networks on Amazon region.. The four collections are relevant to Curt Nimuendaju Technical Reserve Ethnographic Collection at the Goeldi Museum due to their acquisitions during a restructuring and reorganization period, and also, in a way, represent three distinct contexts of collecting indigenous artefacts in Amazon at the end of 19th century and 20th century beginning, led by a French explorer, a Dominican missionary, and a German ethnologist. Their study certainly allows us to analyse how different political and social contexts, religious, philosophical, cultural, scientific thoughts and the relationships between indigenous peoples and collectors acted in objects selection and rejection that make up the aforementioned collections.